2005
DOI: 10.1080/00207450591001871
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tight and Gap Junctional Proteins in the Perineurial Window Model of the Rat Sciatic Nerve

Abstract: Limited perineurial injury, known as a perineurial window, can lead to neuropathic pain. This article hypothesizes that the recovery of the perineurium is associated with the intercellular junctional proteins. It analyzes the expressions of occludin, ZO-1, and connexin 43 by immunoconfocal microscopy. Seven days after injury, immunoreactivities for occludin and ZO-1 were observed, although there was no connexin 43 detected. Then, 21 days after injury, immunoreactivity for connexin 43 were observed. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Detectable signs of recovery process, such as thin perineurial cell layer and first evidence of tight junctions appear within one week, and by three weeks perineurium has tight junction strands and gap junctions. Perineurial window model emphasizes the role of tight junctions in perineurial repair process 51 - 53 . Corresponding results have been shown in the nerve injury model in which ligating rat sciatic nerve for 24h resulted in the recovery of claudin-1 expression in perineurium within two days.…”
Section: Clinical Aspects Of the Peripheral Nerve Barrierssupporting
confidence: 55%
“…Detectable signs of recovery process, such as thin perineurial cell layer and first evidence of tight junctions appear within one week, and by three weeks perineurium has tight junction strands and gap junctions. Perineurial window model emphasizes the role of tight junctions in perineurial repair process 51 - 53 . Corresponding results have been shown in the nerve injury model in which ligating rat sciatic nerve for 24h resulted in the recovery of claudin-1 expression in perineurium within two days.…”
Section: Clinical Aspects Of the Peripheral Nerve Barrierssupporting
confidence: 55%
“…Although plasticity of peripheral gap junctions has been observed following nerve injury (Chandross et al, 1996;Nagaoka et al, 1999;Lin et al, 2002;Ohta et al, 2005), the evidence of their contribution to pain is very limited. A study by Lin et al (2002) suggested a role for Cx37 in neuropathic pain hypersensitivity following peripheral nerve injury through a correlation between the levels of sciatic nerve Cx37 mRNA and the extent of thermal hyperalgesia.…”
Section: Involvement Of Gap Junctions Inmentioning
confidence: 99%
“…Tight junction proteins occludin and ZO-1 as well as gap junction protein connexin 43 were not detectable at 3 days after perineurial window, a surgery method that caused limited peripheral nerve injury. Tight junction proteins occludin and ZO-1 were recovered and re-observed at 7 days after injury while gap junction protein connexin 43 were re-observed after 21 days (Ohta et al, 2005). Gene and protein expressions of claudin-5 and occludin were found to be decreased starting from 3 h after chronic constriction injury of rat sciatic nerves (Moreau et al, 2016).…”
Section: Barrier Alternations Following Peripheral Nerve Injurymentioning
confidence: 99%